Homeobox genes encoding WOX transcription factors in the flowering parasitic plant Monotropa hypopitys - A. V. Shchennikova; O. A. Shulga; E. Z. Kochieva; A. V. Beletsky; M. A. Filyushin; N. V. Ravin; K. G. Skryabin (Вавиловский журнал генетики и селекции)
The formation and maintenance of plant stem cell populations are controlled by the WOX family of homeobox-containing transcription factors. The evolution of WOX genes is considered to be one of the main reasons for flower morphology and plant architecture diversity. The stem cell regulation mechanism is considered to be conserved among flowering plants and most thoroughly studied in Arabidopsis thaliana as a model. The angiosperms morphological diversity implies that there are species-specific features inherent to this mechanism, while the basic signaling is maintained. The unique flowering achlorophyllous mycoheterotrophic plant Monotropa hypopitys obtains nutrients from the tree roots through the mycorrhizal symbiosis. In inductive conditions, the reproductive stem with bracts and an inflorescence at the top is developed from an adventitious root bud. Like other plants, M. hypopitys forms the inflorescence, flower and root meristems, presumably using conserved mechanisms regulating stem cell niche. The study of M. hypopitys homeobox genes should contribute to the knowledge about the function of WOX transcription factors and further understanding of the stem cells control mechanisms in mycoheterotrophic species. The aim of the present study was to analyze M. hypopitys root, bracts and flower transcriptomes obtained from two individual flowering plants. In total, five WOX genes have been identified and characterized by their structure, phylogeny, expression pattern, and possible functions. The assumption is that the MhyWUS1 and MhyWUS2 genes maintain the stem cell population in the inflorescence and flower meristems, MhyWOX13 has a role in the control of root stem cell niche, seed pod formation, flowering initiation, and basic cellular processes, MhyWOX4 functions in the control of cambium stem cells, and MhyWOX2 participates in the differentiation of egg cells and zygotes.